The 8th UICC/AJCC TNM edition for non-small cell lung cancer staging: getting off to a flying start? - Lancia, Andrea; Merizzoli, Elisa; Filippi, Andrea Riccardo (Annals of Translational Medicine; Vol 7, Supplement 6 (September 20, 2019): Annals of Translational Medicine, 2019)
Non-small cell lung cancer (NSCLC) represents the primary cause of cancer death in both men and women (1). Proper disease staging at diagnosis is crucial in providing an accurate prognosis and guiding towards the most appropriate treatment strategy. The Union for International Cancer Control (UICC)/American Joint Committee on Cancer (AJCC) TNM classification has evolved through the years and is the golden standard for solid tumor staging.